Comparative study of CO2 photoreduction using different conformations of CuO photocatalyst: Powder, coating on mesh and thin film - Avila López, Manuel Alejandro; Gavrielides, Stelios; Luo, XiaoJiao; Ojoajogwu, Abah Ezra; Tan, Jeannie Z.Y.; Luévano Hipólito, Edith; Torres Martínez, Leticia Myriam; Maroto Valer, M. Mercedes (Elsevier, 2021)
The use of CuO-based photocatalysts for CO2 photoreduction has been extensively reported in the literature. However, the comparison of the photocatalytic activity and selectivity from the published results becomes difficult due to different experimental conditions (i.e., synthesis method, configuration of photocatalyst, flow rate of gas, water content, light intensity) and reactor geometry employed. Hence, in this work different conformations of CuO-based photocatalyst, namely powder (i.e., synthesized using precipitation, sonochemical and hydrothermal-microwave treatment), coating on glass fiber mesh, and thin film, were tested using the same photoreactor and experimental conditions. All CuO photocatalysts exhibited 100 % product selectivity towards CH4 over CO and the CuO coating on the glass fiber mesh exhibited the highest production of CH4 (56.3 μmol gcat − 1h− 1). The morphology, particle size, particle dispersity, and presence of impurities/defects within the CuO photocatalysts had a significant effect on photocatalytic activity. A numerical model, which was built using COMSOL, revealed that the experimental data obtained in this simulated photocatalytic activity study fitted well, however, further optimization was needed.